The Influence of Service Quality and Ease of Use on Customer Satisfaction Using the Shopee Pay Digital Wallet - Dewi Indriani Jusuf (Journal of Economics and Business (JECOMBI), 2023)
With the development of digital technology and the shift in consumer preferences towards cashless transactions, it is important to understand the factors that influence customer satisfaction with digital payment platforms. This research aims to explore the influence of service quality and ease of use on customer satisfaction in using the Shopee Pay digital wallet. This research method uses a quantitative approach by collecting data from 96 respondents who are active users of the Shopee Pay Digital Wallet in Jatinangor District, Sumedang Regency using a questionnaire distributed via Google Form. The research results show that service quality and ease of use partially influence customer satisfaction for Shopee Pay Digital Wallet users. Simultaneously, service quality and ease of use influence customer satisfaction with Shopee Pay Digital Wallet users by 57.2%.